PROBLEMS FACED BY YOUTH IN INDIA: A REVIEW - Gogoi, Moyuri; Nath , Krishnajyoti (International Journal of Psychosocial Rehabilitation, 2020)
Today’s youth are the future of tomorrow. Youth is the most energetic section of the population of a nation. They hold the capacity to alter the nation at all through the utilisation of their energy. As reported by Census 2011, youth in India constitutes one fifth i.e. 19.1% of the total population and was expected to have 34.33% share of youth in total population by 2020. Hence, India has substantial amount of potentialities which can be manifested in the country’s development as a whole in future. Although Government of India has been constantly evolving policies and programmes for youth welfare;hitherto, youth are facing many serious problems. Thereforeutmost care of this section is need of the hour and for that discussion on the problems of youth is a topic of worth discussion to immediate reach at the solutions. This article is an attempt in this aspect through review of existing literature.